Effect of crop establishment practices on the performance of component cultivars under pigeonpea (Cajanus cajan) - wheat (Triticum aestivum) cropping system in IGP - SINGH, UMMED; PRAHARAJ, C S; SINGH, S S; HAZRA, K K; KUMAR, N (The Indian Journal of Agricultural Sciences, 2018)
Pigeonpea–wheat rotation is emerging as a potential alternative to existing rice–wheat system of Indo–Gangetic plains because of many inherent constraints right from requirements of higher inputs to deterioration in soil health in the latter. Realizing the importance of pigeonpea–wheat cropping system, the present study was conducted to evaluate diverse crop establishment practices [ridge pigeonpea followed by flatbed wheat (RP–FBW); raised–bed pigeonpea followed by raised–bed wheat (RBP–RBW)] in combination with three cultivars of pigeonpea (UPAS 120, ICP 67B, and Pusa 992), and two wheat cultivars (Shatabdi, Unnat Halna). Two–year study revealed that raised–bed practice of crop establishment resulted in 11.7% higher grain yield of pigeonpea as compared to ridge planting. Although the advantage of raised–bed was not apparent in wheat as 13.9% higher grain yield was recorded under flatbed over raised–bed establishment method. Based on pigeonpea equivalent yield and production economics, RP–FBW was found superior over RBP–RBW. However, the performance of component crops suggested that raised–bed for pigeonpea and flatbed for wheat could be the strategic crop establishment under pigeonpea–wheat rotation. Plant nutrient utilization as expressed by nutrient harvest index, physiological efficiency and utilization efficiency differed substantially within the cultivars of pigeonpea and wheat crop; and the preceding pigeonpea cultivars significantly influenced the nutrient acquisition in the successive wheat crop. Among the different cultivars, UPAS 120 pigeonpea followed by Unnat Halna wheat had far better response measured through the highest pigeonpea equivalent yield (2.71 t/ha), net return (` Rs. 69,331), and benefit: cost ratio (2.02). Thus, the study suggested that strategic cultivar selection and appropriate crop establishment method could be the key to maximize output from the pigeonpea–wheat system in IGP.